A 25-Year Trend of Catastrophic Health Expenditure and Its Inequality in China: Evidence from Longitudinal Data - Xu Y; Zhou Y; Pramono A; Liu Y; Jia C (Risk Management and Healthcare Policy, 2022)
Yongjian Xu,1 Yiting Zhou,1 Andi Pramono,2 Yazhuo Liu,1 Cong Jia1 1School of Public Policy and Administration, Xi’an Jiaotong University, Xi’an, People’s Republic of China; 2Community and Aged Care Services, Hunter New EnglAnd Health, NSW, AustraliaCorrespondence: Yongjian Xu, School of Public Policy and Administration, Xi’an Jiaotong University, No. 28 Xianning West Road, Xi’an, 710049, People’s Republic of China, Tel +8618202985437, Email xyjdyx@126.comPurpose: The Chinese government has carried out two major cycles of reform to improve the health system and reduce the disease burden on residents. This study aims to comprehensively track the trends in the occurrence of catastrophic health expenditure (CHE) and its inequality in the past 25 years, which may help better understand the influence of health system reforms on CHE and its inequality.Methods: The study employed the subset of data from China Health and Nutrition Survey conducted from 1991 to 2015. Health payments and net household income were used to calculate CHE. Concentration index and decomposition analysis were used to measure the magnitude of income-related inequality in CHE and decompose it into determinants, respectively.Results: The incidence of CHE in China increased from 3.10% in 1993 to 8.90% in 2004 and still maintained at a high level in the following years. The incidence gap of CHE between the richest and poorest became increasingly wider over year. Moreover, the values of adjusted concentration indexes were all negative in each year, decreasing from − 0.202 in 1991 to − 0.613 in 2015. Income was consistently the largest contributor to the inequality in CHE. The basic medical insurance did not decrease the incidence of CHE and showed the second largest contribution on its inequality before 2004. However, this contribution began to decline after 2006.Conclusion: After the New Health Care Reform, despite many measures taken by the Chinese government, there was still a high incidence of CHE and an increasing inequality from 1991 to 2015. The basic medical insurance in China was not enough to protect households from CHE. The use of big data tools and techniques to effectively screen the poor households, and strengthening the social medical aid system would be helpful to decrease the inequality in CHE.Keywords: catastrophic health expenditure, income-related inequality, concentration index, multilevel model